Internet of things (IoT) based monitoring system for hybrid powered E-bike charging station - Hidayat, Mohammad Noor; Nugroho, Aji; Munir, Abdullah Faiq; Putri, Ratna Ika (Institute of Advanced Engineering and Science, 2025)
The internet of things (IoT) has become an important foundation in the development of web-based and remote technologies. In the implementation of renewable energy in hybrid E-bike systems, IoT-based monitoring system integration has made a significant contribution to monitoring activities. One of the latest innovations in the development of IoT in E-bike systems is the application of power prediction and the Coulomb counting method to estimate the charging time for a battery with a capacity of 200 AH, so that users can know the time needed to charge the battery efficiently. The IoT E-bike system is designed with user data display and monitoring features via the website, such as data on voltage, current, light intensity, battery percentage, power prediction, and prediction of the resulting battery charging time. Experimental results were obtained during the battery charging period, increasing the battery percentage from 50.43% (10 volts) to 71.769% (11.3 volts) in 4.5 hours with a battery charging charge of 153,866.4 C.